Task of leadership for intercultural opening strategies in organizations in adult and continuing education - Sonja Muders; Andreas Martin (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
In view of the growing number of people with a migration background, continuing education organizations are faced with strategic tasks of intercultural opening. These tasks require leaders to initiate and expand integration-promoting teaching work, to promote the intercultural sensitization of the members of the organization, and to develop an intercultural culture. This is a wide issue and concerns leadership action regarding funding, regular and special course programs, training for staff and lecturers, intercultural training, etc. In this qualitative study, the types of intercultural openness adopted by the management of adult education centers were categorized into proactive, reflexive, ambivalent, and symbolic types of openness. Using the procedure of exploratory sequential design, hypotheses were tested with the aim of gaining information that would facilitate broader statements about the field of adult education providers. The quantitative distribution was analyzed using a data set called 'wbmonitor' and a regional data set.
Keywords: 330; Intercultural opening strategy; Leadership; Organizations in adult and continuing education (OACEs); Adult education centers (AECs); Effects of migration on participation in continuing education